Aplicação da farinha de maracujá como substituto funcional da farinha de trigo em petit gateau - COMELLI, Renan Monteiro; SOUZA, Ricardo Nobre Granda de; AMORIM, Pedro Lucas Ribeiro Salvador; OLIVEIRA, vinícius Rogério de (075, 2025)
Este estudo avaliou a viabilidade da substituição da farinha de trigo por farinha de casca de maracujá comercial na elaboração de petit gâteau, visando ao desenvolvimento de uma alternativa sem glúten, funcional e sensorialmente aceita. Foram produzidas duas formulações simultâneas, variando apenas o tipo de farinha, e submetidas à análise sensorial com 16 avaliadores não treinados. A versão com farinha de casca de maracujá apresentou aroma mais intenso, textura interna mais úmida e leve amargor, enquanto a formulação tradicional demonstrou maior doçura e textura uniforme. Apesar das diferenças percebidas, ambas foram bem aceitas, evidenciando que a substituição é tecnologicamente viável e não compromete a qualidade sensorial da sobremesa. A utilização da farinha de casca de maracujá amplia as possibilidades de inclusão alimentar para indivíduos celíacos e contribui para o aproveitamento sustentável de subprodutos agroindustriais.

The development of artisanal food products has gained prominence in the agro industrial sector due to the increasing consumer demand for foods with regional identity and distinctive sensory characteristics. In this context, the present study aimed to develop and evaluate the sensory acceptance of an artisanal sandwich composed of homemade bread, shredded cured beef (carne seca) and mozzarella cheese. The preparation involved standardized steps including dough development, meat desalting and cooking, shredding, and incorporation of grated mozzarella as a binding component of the filling. Sensory acceptance testing was carried out with untrained panelists using a nine-point structured hedonic scale to assess color, aroma, flavor and overall impression. The results demonstrated high levels of acceptance for all evaluated attributes, with aroma and flavor receiving the highest scores. The overall acceptance exceeding 80% indicates good commercial potential and suitability for local markets and agro-industrial fairs. The findings support that the artisanal sandwich developed in this study presents satisfactory sensory quality, a well-balanced filling and positive consumer perception, establishing it as a promising alternative for expanding artisanal food products within the agro-industrial context.
Keywords: Farinha de trigo; Maracujá; Recursos Naturais